Electrospun TiO2/SnO2 nanofibers with innovative structure and chemical properties for highly efficient photocatalytic H2 generation - Lee, Siew Siang (2013)
Innovative TiO2/SnO2 nanofibers were fabricated via electrospinning an innovated precursor solution and used for photocatalytic H2 generation. The nanofibers exhibited greatly enhanced H2 evolution rate compared to bare TiO2 nanofiber and P25. The enhanced efficiency of the TiO2/SnO2 nanofibers was attributed to its excellent synergistic properties: (1) its good mesoporosity; (2) the red-shift of absorbance spectra to enhance light absorbance capability; (3) its long nanofibrous structure and (4) anatase TiO2 – rutile TiO2 – rutile SnO2 ternary junctions favorable for the separation of electrons and holes. Based on our experimental results, the optimum ratio of TiO2/SnO2 nanofibers with 3% Sn demonstrated the highest efficiency in H2 generation.